Type I interferon signaling controls the early hematopoietic expansion in response to β-glucan - Yangsong Xu; Man K.S. Lee; Nicole A. de Weerd; Ziyue Fu; Camilla Bertuzzo Veiga; Dragana Dragoljevic; Dmitri Sviridov; Paul J. Hertzog; Andrew J. Fleetwood; Andrew J. Murphy (iScience)
Summary: Rapid hematopoietic adaptations are important for building and sustaining the biological response to β-glucan. The signals involved in these early events have not yet been fully explored. Given that type I interferons are produced in response to β-glucan and can profoundly impact hematopoietic stem cell (HSC) function, we hypothesized that this pathway may be involved in the early bone marrow response to β-glucan. In vivo administration of β-glucan led to local interferon-α production in the peritoneal cavity and bone marrow, upregulation of its receptor, IFNAR1, specifically on long-term hematopoietic stem cells (LT-HSCs), and broad expansion of downstream progenitor subpopulations. We demonstrate that intact type I interferon signaling is critical for β-glucan-mediated LT-HSC proliferation, mitochondrial activity, and glycolytic commitment. By determining that type I interferon signaling is important for LT-HSCs, which sit at the apex of the hematopoietic hierarchy, we uncover an important component of the early inflammatory response to β-glucan.